2000
DOI: 10.1159/000017241
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Dementia in Primary Care: The Linköping Study

Abstract: We examined to what extent dementia and cognitive impairment are detected in a primary health care centre. A systematic sample of patients aged 70 years and above, who attended a primary health care centre for a doctor’s consultation (n = 350) were examined with a neuropsychiatric examination and an interview with a close informant. Dementia was diagnosed according to DSM-III-R. Medical records from the health centre were examined for entries on cognitive decline or dementia, other diagnoses and prescribed dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
82
2
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(94 citation statements)
references
References 19 publications
7
82
2
3
Order By: Relevance
“…The GPs in our study underestimated the occurrence of dementia, indicating many undetected patients, which is in line with our previous study (14).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The GPs in our study underestimated the occurrence of dementia, indicating many undetected patients, which is in line with our previous study (14).…”
Section: Discussionsupporting
confidence: 93%
“…Most of the responders were experienced and had a high proportion of elderly in their practice -conrmed in our previous study, where 40% of attendees were elderly (6,14).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…In other words, there is a high probability of the development of dementia in people with cognitive problems in the coming years (2,11). Studies in high income countries show that only one-fifth to one-half of dementia cases are typically recognized and documented in primary care (12)(13)(14)(15)(16). This treatment gap is much greater in low and middle income countries; one study in India showed that 90% remain unidentified (17).…”
Section: Contextmentioning
confidence: 99%